Komunikasi Love Language Anak Autisme dengan Orang Tua - Krisjanto Kusuma, Angelina Maria; Aulia, Sisca (Koneksi, 2024)
The concept of Love Language serves as a foundation for understanding how children with special needs, specifically those with autism, communicate affection towards their parents and vice versa. Autism, as a genetic syndrome, often poses challenges to family dynamics, particularly in communication and expressing love towards family members due to the communication impairments associated with autism. The aim of this research is to examine how Love Language communication occurs between children with autism and their parents. Interpersonal Communication serves as the theoretical basis to explore how the Five Love Languages form the basis of communication in expressing affection between autistic children and their parents. The applied research methodology is qualitative and descriptive. Data collection involves interviews with families having a first-level autistic child and observations of interaction patterns between autistic children and their parents. The analysis of Love Language is used to understand the communication of affection between autistic children and their parents. The results indicate that the most commonly used Love Languages from children to parents are Quality Time (spending time together) and Physical Touch (physical contact). On the other hand, parents' Love Languages towards their autistic children include Acts of Service (providing assistance) and Quality Time (spending time together). Konsep Love Language menjadi landasan untuk memahami bagaimana cara komunikasi anak berkebutuhan khusus autisme dalam mengekspresikan kasih sayang anak kepada orang tua mereka dan juga sebaliknya. Autisme sebagai sindrom genetik sering menjadi tantangan dinamika keluarga dalam berkomunikasi terutama dalam mengekspresikan kasih sayang kepada anggota keluarga dikarenakan autisme sendiri merupakan sebuah gangguan anak dalam kemampuan berkomunikasi. Tujuan dari penelitian ini untuk melihat bagaimana komunikasi Love Language dari anak berkebutuhan khusus autisme dengan orang tua mereka. Komunikasi Interpersonal menjadi landasan teori untuk mengeksplorasi bagaimana Five Love Languages menjadi sebuah dasar komunikasi dalam mengekspresikan kasih sayang antara anak autisme kepada orang tua dan sebaliknya. Metodologi penelitian yang diterapkan adalah kualitatif deskriptif, di mana pengumpulan data menggunakan teknik wawancara kepada keluarga yang memiliki anak autisme tingkat satu dan melakukan observasi kepada pola interaksi antara anak autisme dengan orang tuanya. Dari hasil penelitian ini analisis Love Language digunakan sebagai komunikasi pengekspresian kasih sayang antara anak autisme dengan orang tua. Dari anak kepada orang tua yang paling digunakan adalah Quality Time atau menghabiskan waktu bersama dan Physical Touch atau pemberian sentuhan, sedangkan love language yang digunakan dari orang tua dengan anak autisme adalah Act of service atau memberikan pelayanan dan Quality Time atau menghabiskan waktu bersama.